Physical and structural properties and thermal behaviour of starch-poly(ɛ-caprolactone) blend films for food packaging. (September 2015) - Ortega-Toro, Rodrigo; Contreras, Jessica; Talens, Pau; Chiralt., Amparo
Highlights: Small degree of PCL miscibility in the starch phase was detected. Partial inhibition of amylose retrogradation during film storage was manifested. Small PCL ratios increased the elastic modulus of the starch-based films. Abstract: Structural and physical properties (barrier, mechanical, and optical properties) and thermal behaviour of corn starch-PCL blend films, containing glycerol as plasticizer, obtained by compression moulding, at 160 °C and 130 bars, were studied. The stability on the films' properties was also evaluated. Blend films showed phase separation of the polymers in a heterogeneous matrix with starch rich regions and PCL rich regions. Nevertheless, a small miscibility of PCL in the starch phase was detected trough the shift in the glass transition temperature of the starch phase, which leads to a partial inhibition of amylose crystallization during film formation and storage. The lack of interfacial adhesion of PCL and starch phases promoted films' fragility and reduced stretchability, although elastic modulus of the films with small PCL ratios increased. Water barrier properties of starch films were improved as the PCL increased in the blend, but oxygen permeability increased. Due to the food compatibility of this polymer blends (without any toxic compound) these could be an interesting alternative for food packaging, where some drawbacks of starch films has been overcome.